2016
DOI: 10.1002/2015jg003217
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial respiration rate and temperature sensitivity along a north‐south forest transect in eastern China: Patterns and influencing factors

Abstract: Soil organic matter is one of the most important carbon (C) pools in terrestrial ecosystems, and future warming from climate change will likely alter soil C storage via temperature effects on microbial respiration. In this study, we collected forest soils from eight locations along a 3700 km north-south transect in eastern China (NSTEC). For 8 weeks these soils were incubated under a periodically changing temperature range of 6-30°C while frequently measuring soil microbial respiration rate (Rs; each sample ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 65 publications
(99 reference statements)
1
37
1
Order By: Relevance
“…); C is the slope of the change in CO 2 concentration; V is the volume of the incubation bottle and gas tube; m is the soil weight (g); α is the conversion coefficient for CO 2 mass (12/44, from CO 2 to C); and β is a conversion coefficient of time (3600, from s to h) (Wang et al, 2016). …”
Section: Measurement Of Soil Microbial Respiration Rate (R S )mentioning
confidence: 99%
“…); C is the slope of the change in CO 2 concentration; V is the volume of the incubation bottle and gas tube; m is the soil weight (g); α is the conversion coefficient for CO 2 mass (12/44, from CO 2 to C); and β is a conversion coefficient of time (3600, from s to h) (Wang et al, 2016). …”
Section: Measurement Of Soil Microbial Respiration Rate (R S )mentioning
confidence: 99%
“…5). Chemical properties (pH, ORP), substrate (DOC), and temperature primarily exerted an influence on Q 10 by regulating microbial activity (Wang et al, 2016). Similarly, Wei et al (2014) confirmed that Q 10 depends on the structure of the soil microbial community.…”
Section: Soil Microbial Properties Control the Responses Of Q 10mentioning
confidence: 48%
“…2). R S and soil temperature were simultaneously and continuously measured during the model of varying temperature over 24-h based on the program of Wang et al (2016). Measuring R S more frequently (i.e., at intervals of several minutes) allows for an improved exploration of the relationship between R S and changing temperatures, as well as a more accurate calculation of Q 10 .…”
Section: Laboratory Incubation and Analysismentioning
confidence: 99%
See 2 more Smart Citations